AB1008 Prevalence of fibromyalgia in Inflammatory Rheumatic Disease. Single-Center Cross-Sectional Study in 691 Patients. (15th July 2016) - Fan, A.; Tournadre, A.; Pereira, B.; Tatar, Z.; Couderc, M.; Malochet-Guinamand, S.; Sylvain, M.; Soubrier, M.; Dubost, J.-J.
Abstract : Background: Fibromyalgia (FM) is a prevalent syndrome in patients with inflammatory rheumatic disease. Objectives: The purpose of this study was to evaluate and compare the prevalence of FM in various inflammatory rheumatic diseases. Methods: This single-center cross-sectional study was conducted between September 2014 and April 2015. We screened for clinical signs of fibromyalgia in all patients presenting for rheumatoid arthritis (RA), spondyloarthritis (SpA), and connective tissue disease (Sjögren's syndrome (SS), systemic lupus erythematosus (SLE), scleroderma (Scl), myositis). Diagnosis of FM was based on ACR–90 classification criteria (to minimize interfering overlap between rheumatic disease-related pain and FM-related pain) and expert opinion. Results: In total, 691 patients were included in the study: 325 RA, 298 SpA (59 psoriatic arthritis, 137 radiographic axial SpA, 64 non-radiographic axial SpA, 38 peripheral SpA), 28 SLE, 27 SS, 14 Scl, and 6 myositis. The population counted 451 women (65.3%) and 240 men (34.7%). Mean all-population age was 55.8±15.5 years. Median disease duration was 11 years [IQR 5–20]. In the total population, 55 patients (8%) met the ACR–90 criteria, and 97 patients (14%) were given a diagnosis of FM by the expert doctor. Prevalence of FM meeting ACR–90 criteria was 4.9% in RA, 11.1% in SpA, and 11.3% in connective tissue disease, and was significantly higher in the SpA group than in the RA group ( p =0.05). The expert settled on a diagnosis of FM for 7.7% of patients with RA, 17.5% of patients with SpA, and 28.2% of patients with connective tissue disease. The expert diagnosed significantly more FM in SpA ( p =0.003) and connective tissue disease ( p =0.001) than in RA. Conclusions: Concomitant fibromyalgia is prevalent in inflammatory rheumatic disease, especially in spondyloarthritis and connective tissue disease. The expert doctor makes the diagnosis of fibromyalgia more often than ACR–90 criteria. Disclosure of Interest: None declared